The demonstrative THAT and the elaboration of reference: a case of linguistic accommodation - Élise Mignot (Anglophonia, 2018)
We examine the determiners and pronouns THIS and THAT, concentrating mostly on THAT, which, according to our data, signals that the reference or, in some cases, the process of categorization, is in progress (whereas with THIS, reference and categorisation are stable). One indication of that is the greater length of THAT noun phrases. Others are the contexts in which THAT occurs, e.g. definitions, or the creation of a sub-category. Our set of data is taken from the novel Lolita (Nabokov 1955), in which we conducted an inventory of THIS and THAT noun phrases (877 occurrences).